Prelithiated V2C MXene: A High‐Performance Electrode for Hybrid Magnesium/Lithium‐Ion Batteries by Ion Cointercalation - Liu, Fanfan; Liu, Yongchang; Zhao, Xudong; Liu, Kunyang; Yin, Haiqing; Fan, Li‐Zhen (Small (Weinheim an der Bergstrasse, Germany), 2020)
The pursuit of high reversible capacity and long cycle life for rechargeable batteries has gained extensive attention in recent years, and the development of applicable electrode materials is the key point. Herein, thanks to the preintercalation of lithium ions, a stable and highly conductive nanostructure of V2C MXene is successfully fabricated via a facile self‐discharge mechanism, which provides open spaces for rapid ion diffusion and guarantees fast electron transport. Taking the prelithiated V2C as electrode, an outstanding initial coulombic efficiency of 80% and an impressive capacity retention of ≈98% after 5000 charge/discharge cycles are achieved for lithium‐ion batteries. Especially, it demonstrates a fascinating reversible capacity of up to 230.3 mA h g−1 at 0.02 A g−1 and a long cycling life of 82% capacity retention over 480 cycles in the hybrid magnesium/lithium‐ion batteries. In addition, the Mg2+ and Li+ ions cointercalation mechanism of the prelithiated V2C is elucidated through ex situ X‐ray diffraction and X‐ray photoelectron spectroscopy characterizations. This work not only offers an effective approach to compensate the large initial lithium loss of high‐capacity anode materials but also opens up a new and viable avenue to develop promising hybrid Mg/Li‐storage materials with eminent electrochemical performance. Prelithiated V2C MXene with a stable and highly conductive nanostructure is prepared through a facile self‐discharge mechanism. The preintercalation of Li+ enables improved initial coulombic efficiency and enhances cycling performance in Li‐ion batteries; exceptional rate capability and unprecedentedly long cycling life are also achieved for Mg2+/Li+ cointercalation chemistry.